Back and neck pain prevalence and their association with physical inactivity domains in adolescents - Scarabottolo, Catarina Covolo [UNESP]; Pinto, R. Z. [UNESP]; Oliveira, C. B. [UNESP]; Zanuto, E. F. [UNESP]; Cardoso, J. R.; Christofaro, D. G.D. [UNESP] (Springer Nature, 2017)
Purpose: Back pain affects people of all ages. This may be associated with physical inactivity, and in the case of physical activity in different domains, the relationship with back pain is not clear in the literature. The aim of this study was to estimate the prevalence of low back and neck pain and investigate their association in different domains of physical inactivity. Methods: 1011 randomly selected students participated in this study. Neck and back pain were assessed using the Nordic questionnaire, whereas the Baecke Physical Activity questionnaire was used to measure physical activity domains. Separate Binary Logistic Regression models were performed to investigate the association of physical activity domains with neck or back pain. Results: 17.4% of the students reported cervical pain, while 18.0% reported low back pain. Older adolescents had a higher prevalence of cervical pain (24.4%) than younger adolescents (11.9%) (p value <0.001), as well as lumbar pain, being 25.1% in older adolescents and 12.4% in younger (p value <0.001). Adolescents physically inactive in the school environment were less likely to have pain in the cervical region [OR 0.67 (0.44–0.99)] or back pain [OR 0.60 (0.40–0.91)]. Being inactive in occupational activities was associated with cervical pain [OR 1.49 (1.06–2.10)]. Being inactive in the sports environment presented a marginal relationship with pain in the cervical region [OR 1.41 (0.99–2.02)]. Conclusions: The prevalence of neck and low back pain was higher in older adolescents and physical inactivity in the sporting context and occupational activities could be a risk factor to increase the chances of back pain.
Keywords: Adolescent; Back pain; Physical inactivity; Students